Equitable access to quality trauma systems in low-income and middle-income countries: assessing gaps and developing priorities in Ghana, Rwanda and South Africa - Justine I Davies; Antonio Belli; Kathryn Chu; Stephen Tabiri; John Whitaker; Maria Lisa Odland; Anthony Howard; Abebe Bekele; Agnieszka Ignatowicz; Barnabas Alayande; Abdul-Malik Abdul-Latif; Bernard Appia Ofori; et al. (BMJ Global Health, 2022)
Injuries in low-income and middle-income countries are prevalent and their number is expected to increase. Death and disability after injury can be reduced if people reach healthcare facilities in a timely manner. Knowledge of barriers to access to quality injury care is necessary to intervene to improve outcomes. We combined a four-delay framework with WHO Building Blocks and Institution of Medicine Quality Outcomes Frameworks to describe barriers to trauma care in three countries in sub-Saharan Africa: Ghana, South Africa and Rwanda. We used a parallel convergent mixed-methods research design, integrating the results to enable a holistic analysis of the barriers to access to quality injury care. Data were collected using surveys of patient experiences of injury care, interviews and focus group discussions with patients and community leaders, and a survey of policy-makers and healthcare leaders on the governance context for injury care. We identified 121 barriers across all three countries. Of these, 31 (25.6%) were shared across countries. More than half (18/31, 58%) were predominantly related to delay 3 (‘Delays to receiving quality care’). The majority of the barriers were captured using just one of the multiple methods, emphasising the need to use multiple methods to identify all barriers. Given there are many barriers to access to quality care for people who have been injured in Rwanda, Ghana and South Africa, but few of these are shared across countries, solutions to overcome these barriers may also be contextually dependent. This suggests the need for rigorous assessments of contexts using multiple data collection methods before developing interventions to improve access to quality care.